A novel supramolecular polymer gel-based long-alkyl-chain-functionalized coumarin acylhydrazone for the sequential detection and separation of toxic ions. Issue 4 (19th December 2019) - Hu, Jing-Han; Yin, Zhi-Yuan; Gui, Kai; Fu, Qing-Qing; Yao, Ying; Fu, Xu-Mei; Liu, Hui-Xin
Abstract : A novel long-alkyl-chains functionalized supramolecular polymer gel OGC was constructed, which shows successive recognition of CN − and S 2− to Fe 3+ and Ag + . So, our study provided a new methods to detect deferent toxic ions via single chemosensor. Abstract : A novel approach for the detection and separation of toxic ions was successfully developed via the introduction of competitive reactions into a long-alkyl-chained acylhydrazone-based coumarin supramolecular polymer, chemosensor OGC (3%, n -BuOH/H2 O), which showed sequential detection and separation of CN −, Fe 3+ and S 2−, Ag + in the gel state with high selectivity and sensitivity. Moreover, the ion-responsive films were prepared for the convenient and continuous detection of CN −, Fe 3+ and S 2−, Ag + in water solution.